2018
DOI: 10.5455/ijlr.20170817043618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementing Spirulina and Thyme on Nutrient Digestibility and FCR in New Zealand White Rabbits

Abstract: An experiment was conducted on 48 New Zealand White rabbits of either sex for evaluating the effect of supplementing spirulina and thyme on nutrient digestibility and feed conversion ratio (FCR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In addition, all results indicated that the feeding values of the rations reflected the positive effect of the addition of SP on nutrient digestibility; especially the higher SP levels. According to Singh et al [29] the addition of SP to the rabbit rations improved the TDN and DCP values. Conversely, Hassan et al [30] found the dietary values of growing rabbit diets were not affected by adding zinc-or selenium-enriched SP or their combination supplementation.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, all results indicated that the feeding values of the rations reflected the positive effect of the addition of SP on nutrient digestibility; especially the higher SP levels. According to Singh et al [29] the addition of SP to the rabbit rations improved the TDN and DCP values. Conversely, Hassan et al [30] found the dietary values of growing rabbit diets were not affected by adding zinc-or selenium-enriched SP or their combination supplementation.…”
Section: Discussionmentioning
confidence: 95%